ANALISIS KINERJA BANK SWASTA NASIONAL DEVISA DAN NON DEVISA DI INDONESIA - Sarwoko, Endi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2009)
This research aims to know the description of foreign exchange commercial banks and non-foreign exchange commercial banks performance in Indonesia. It also tries to analyze the performance differences of the foreign exchange commercial banks and non-foreign exchange commercial banks in Indonesia. The performance indicators involve CAR, BOPO, NIM, NPL, and LDR ratios. The kinds of data used in this study are secondary data involving Indonesian Banking Statistics in the year 2000 until 2008. The used methods of analysis are non-parametric statistic (Mann-Whitney U). The results of the analysis show that there are significant differences of performance foreign exchange commercial banks and non-foreign exchange commercial banks analyzed through LDR and NIM ratios. Non-foreign exchange commercial banks have more important role in running intermediation function show by LDR ratio. The non-foreign exchange commercial banks show higher in this aspect of analysis. In addition, non-foreign exchange commercial banks own an ability to produce interest better and to utilize the owned assets. Therefore, the non-foreign exchange commercial banks operate more efficiently compared with the foreign exchange commercial banks.